On the Convergence of a Weak Greedy Algorithm for the Multivariate Haar Basis - Dilworth, S. J.; Gogyan, S.; Kutzarova, Denka (Constructive approximation, 2014)
We define a family of weak thresholding greedy algorithms for the multivariate Haar basis for L 1 [0,1] d ( d ≥1). We prove convergence and uniform boundedness of the weak greedy approximants for all f ∈ L 1 [0,1] d .